Exact and numerical traveling wave solutions of Whitham-Broer-Kaup equations - El-Sayed, SM; Kaya, D (Elsevier Science Inc, 2005)
In this paper, we find the explicit and numerical traveling wave solutions of Whitham-Broer-Kaup (for short WBK) equations, which contain blow-up solutions and periodic solutions, by using the decomposition method. By using this method, the solutions were calculated in the form of a convergent power series with easily computable components. The convergence of the method as applied to the Whitham-Broer-Kaup equations is illustrated numerically. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: the Adomian decomposition method; the Whitham-Broer-Kaup equation; traveling wave solution; blow-up solution; periodic solution